External examination in France and Germany: recognition of informal learning from an institutional economic perspective. (7th June 2010) - Annen, Silvia; Schreiber, Daniel
Against the background of increasing importance of informal learning, in this paper, the national approaches towards the recognition of informal acquired competences in France Validation des Acquis de l'Experience (VAE) and Germany (external examination) are compared. As a theoretical and conceptual access, the new institutional economics is chosen. The context of the recognition of the problems concerning the transparency of the competences to be recognised arises as well, concerning the transparency of the according methods. In terms of the principal agent theory these problems can be seen as information asymmetries. To reduce them, stakeholders can choose methods of either signalling or screening. Therefore, both national approaches are analysed concerning the methods of the stakeholders. Furthermore, central similarities and differences are extracted.